The Role of Islamic Sharia in Family Structure and Relationships - Sanar Sewar Sewar (QALAAI ZANIST JOURNAL, 2024)
This research explores "The Role of Islamic Sharia in Family Structure and Relationships." The study provides a comprehensive analysis of the concepts and principles governing family life in Islam. It emphasizes the significance of a Sharia-compliant marriage as the foundation for family building and illustrates how Sharia guides marital and parental relationships based on principles of justice and equality. The research underscores the rights and responsibilities of individuals within the family. Additionally, it delves into the Islamic ethics and values that form the basis of family relationships. The research draws support from Quranic verses and Prophetic traditions, highlighting the role of Islamic Sharia in constructing families grounded in social justice and stability